What is the effect of the legalization of marijuana on prescription opioid‐related adverse events?. Issue 5 (May 2018) - Mooney, Emanuela; Thompson, Angela
Abstract : EVIDENCE‐BASED ANSWER : Legalization of medical marijuana may be associated with a reduction in hospitalization rates because of opioid dependence or abuse by 23%, hospitalizations related to opioid overdose mortality by 13%, and opioid overdose mortality by 25% (SOR: B, retrospective cohort studies).